If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1x + 8 = 10x + 89 Reorder the terms: 8 + -1x = 10x + 89 Reorder the terms: 8 + -1x = 89 + 10x Solving 8 + -1x = 89 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 8 + -1x + -10x = 89 + 10x + -10x Combine like terms: -1x + -10x = -11x 8 + -11x = 89 + 10x + -10x Combine like terms: 10x + -10x = 0 8 + -11x = 89 + 0 8 + -11x = 89 Add '-8' to each side of the equation. 8 + -8 + -11x = 89 + -8 Combine like terms: 8 + -8 = 0 0 + -11x = 89 + -8 -11x = 89 + -8 Combine like terms: 89 + -8 = 81 -11x = 81 Divide each side by '-11'. x = -7.363636364 Simplifying x = -7.363636364
| 9x^2+3x^3=0 | | y=1x+140 | | 6x+18=4x+124 | | -16+8y=2y+20 | | 2x+2x^2+2y^2-30=0 | | 5x+25=5x+15 | | 100=10ln(x+2)+50 | | 128+16s-4s^2= | | (3x-4)+(3x+10)-(2x-4)=6 | | 1x+4y=52263 | | p=3(1+3x) | | 6-5/4x1 | | 581+840y+295y^2=0 | | -2(1-5x)=-(x+1) | | 360+96k=0 | | -2(x+4)+5= | | x+2=7y | | 3x^2-12=0 | | 96=94p | | x-5/3=6 | | 50.50+18n= | | 2c+8=81 | | [2x+9]-10=5 | | -12-(x-3)=4x+5 | | 12+(3-2x)=-x | | X=(3)2 | | x^2+x+2=0 | | 12+(2x-3)=-x | | 3x^2-6y-39=0 | | 2x^2-2x-24=0 | | 3x^2-18x-39=0 | | 3x^2-18x+-9=0 |